Financiamento do Sistema Único de Saúde no Estado da Bahia - Teles, Andrei Souza (2015)
The health care financing consists of a structural and structuring element that underpins economic social practices that take care of human life. Considering the importance of funding the conduct, implementation and success of health policies, this work aimed to analyze the Public Expenditure of the Unified National Health System (SUS) in the state of Bahia, from 2009 to 2012. It is a quantitative study of a descriptive and analytical perspective, comparative and retrospective, covering all 417 municipalities in Bahia. The main data on funding for the health sector were declared by municipalities to Information System Public Health Budgets (SIOPS), collected between 2013 and 2014, and tabulated with the help of the National Health Accounts model (National Health Accounts - NHA), specifically using the Table 1 (Funding Sources for Finance Professionals), which was adapted to the reality of funding and Brazilian information systems. The results revealed that in Bahia public spending on the SUS, accumulated over four years of study, was about R$ 29,23 billion, 30% of which (8,66 billion) for the year 2012. In considering only the resources declared by municipalities to SIOPS, expended by the three spheres of government, there was an increase of 50,58% in the Public Expenditure on Health (GPS), totaling in the period from R$ 17,105 billion. The macro-East draws attention to the large volume of spending, surpassing the mark of R$ 1 billion every year, and two of its health regions, Salvador and Camaçari, have been in the GPS ranking apex in the period. The health expenditure by size analysis showed that the vast majority of municipalities, about 70% did not reach the level of R$ 5 million. It was found in 2010 that 20% of resources, about R$ 410,30 million, were transferred to the 219 municipalities with the lowest Municipal Human Development Index (IDHM) the state, on the other hand, the 37 cities with the best IDHM received approximately 60% of federal funds, that is, more than R$ 1,23 billion. It was evident also that 30% of resources, approximately R$ 615,45 million, was allocated to 40% of the population, which is spread over 348 municipalities of the total of 417 present in Bahia and 50%, equivalent to more than R$ 1 billion, were also transferred to 40% of the population, but that is distributed in only 17 municipalities. With regard to the volume of federal funds specifically for the Mobile Emergency Service (SAMU), from 2009 to 2012, noted an increase of 148,31%, highlighting the East macro-region. However, half of the state health regions did not show whether spending records with this service. The relative share of SAMU as Average funding block component and high complexity grew in the period, reached 6,67% in 2012. Data analysis identified the existing inequalities in the distribution of resources among regions, health regions and municipalities in the state of Bahia, but also inequalities, as municipalities and regions were favored already privileged socioeconomic at the expense of locations where populations are greater risks of illness and death, which remained being contemplated with proportionally fewer resources in relation to their health needs. It is not intended to generalize these results, but it is expected this study to contribute in the formulation of health policy, planning and management of resources within the SUS.